Summary (Scottish Historical and Archaeological Internet Reports, 2008)
Rescue excavations in advance of gravel quarrying were carried out under the direction of the late Eric Cregeen from 1960 to 1962, at Bruach an Druimein, Poltalloch, Mid Argyll (NGR: NR 820 972). The site lies on one of the fluvio-glacial terraces which border the Kilmartin Glen, overlooking the lower ground, which has one of the densest concentrations of prehistoric funerary monuments in Britain. The excavations were carried out in difficult circumstances, with little good stratigraphy, and proved difficult to bring to publication. The present report is based on the substantial records created by Cregeen, including draft reports, and further working of the site archive by his sister, Sheila Cregeen. The site had previously been identified as containing later prehistoric and Early Historic cist burials and a degraded bank. The main features of the excavated part of site were an enclosing ditch complex, and numerous post-holes and other occupation evidence within the ditch. Possible Neolithic/Bronze Age activity was indicated by lithic scatters and possible burnt mound material. Several Bronze Age cist-burials, also uncovered during the quarrying, have already been published. The main phase of occupation, as supported by a series of radiocarbon dates, lay in the later first millennium BC, the early Iron Age period. The post-holes were interpreted as belonging to at least two roundhouses, important as the first such structures identified in Atlantic Scotland, though common in eastern and southern Britain. Evidence of cereal production of hulled six-row barley was abundant, but few artefacts could be confidently assigned to this phase, which was aceramic. Rare evidence of prehistoric woodland management in the form of hazel coppicing was deduced from the charcoal samples. The initial construction and use of the ditch complex was dated to this period, though it could have been re-utilized in the succeeding periods. There was a further significant phase of occupation in the Early Historic period. No certain structures were excavated, but series of intermittent patches of walling, and considerable spreads of artefacts and non-ferrous metalworking debris, suggested the presence of a craft-working area. The finds ranged in date from the seventh to 10th century AD, contemporary with the main period of occupation of the important royal site of Dunadd, situated 4km to the south-east. Two beads and other finds indicated close contact between the two sites, and a motif piece showing Norse-style ornament is important as there is otherwise little evidence of Norse influence in this area. The nature of the Early Historic settlement remains unclear, with some evidence of ecclesiastic activity in the form of long-cist graves, an ogham inscription, and a Kil- placename. Later medieval activity in the area is indicated by a spread of medieval pottery in the ploughsoil, unusually including evidence of material imported from lowland Scotland and possibly the Continent. Finally, a standing stone was erected in the 19th century. The site is important in giving a rare glimpse of settlement activity on the low-lying land of the region, rather than the hilltop settlements and funerary monuments which have dominated our view of the Kilmartin Glen until now.\r